Analysis of dual-flow plates with a large free section - Taranenko, Gennadiy (Technology audit and production reserves, 2020)
The object of research is the dual-type plates with a large free section. One of the most problematic areas of such plates is their low efficiency, which depends on the operating mode of the dual-type plates with a large free section. The gas-liquid layer on such plates is represented by drops and films of liquid, which are the dispersed phase. In this case, the continuous phase is gas. Insufficient liquid supply on dual-flow plates with a large free section leads to a decrease in the efficiency of such plates. During the research, the method of hydrodynamic modeling was used. This method consists in the fact that the dual-flow plates are investigated first in experimental installations, and their results, according to a certain method, are used to calculate industrial plates. A study of dual-flow plates with a large free section in a wide range of gas and liquid loads has been carried out. The range of work of the plates has been determined. It has been established that the hydraulic resistance of the dual-flow plates with a large free section depends little on the diameter of the column apparatus. An almost complete coincidence of the dependence of the height of the gas-liquid layer on the gas velocity in the column cross-section is shown for dual-flow plates with a large free section installed in columns with diameters D=0.057, 0.4 and 2 m. It is revealed that a column with a diameter of D=0.057 m can be used to simulate the operation of dual-flow plates with a large free section of industrial diameter. For example, for dual-flow plates of the usual free section during hydrodynamic modeling, it is necessary to use pilot plants with columns of larger diameter D=0.15–0.25 m with a large free cross-section can operate at significantly higher gas and liquid velocities compared to the dual-flow plates with a conventional free cross-section. The use of dual-flow plates with a large free section is recommended in absorption processes at high irrigation densities.